2016
DOI: 10.1038/nrc.2016.108
|View full text |Cite
|
Sign up to set email alerts
|

Cancer nanomedicine: progress, challenges and opportunities

Abstract: The intrinsic limits of conventional cancer therapies prompted the development and application of various nanotechnologies for more effective and safer cancer treatment, herein referred to as cancer nanomedicine. Considerable technological success has been achieved in this field, but the main obstacles to nanomedicine becoming a new paradigm in cancer therapy stem from the complexities and heterogeneity of tumour biology, an incomplete understanding of nano–bio interactions and the challenges regarding chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
3,309
2
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 4,484 publications
(3,484 citation statements)
references
References 244 publications
12
3,309
2
17
Order By: Relevance
“…Dozens of nanomedicines, such as Doxil, have been approved by the Food and Drug Administration (FDA) 12. However, the nanoscale size of these nanomedicines critically restricts their penetration in the dense ECM of hypoxic solid tumors, delivery efficiency, and antitumor efficacy 13.…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of nanomedicines, such as Doxil, have been approved by the Food and Drug Administration (FDA) 12. However, the nanoscale size of these nanomedicines critically restricts their penetration in the dense ECM of hypoxic solid tumors, delivery efficiency, and antitumor efficacy 13.…”
Section: Introductionmentioning
confidence: 99%
“…[210] Recently, liposomal-based nanomedicines combining cytarabine and daunorubicin (Vyxeos/CPX-351) in clinical trial phase III have shown improved overall survival benefits in patients with high risk acute myeloid leukaemia, increased from 5.95 to 9.56 months. [14] Thus, these nanomedicines can only provide modest overall survival benefits to the patients. The majority of the clinically approved cancer nanomedicines are based on the concept of EPR, while some of them designed with ligand mediated active targeting to alter the behaviour in tumors are [203] in clinical trials, such as BIND-014 (Bind therapeutics), [211] MM-302 (Merrimack Pharmaceuticals), [212] and anti-EGFR immunoliposomes.…”
Section: Cancer Nanomedicines From the Clinical Medicine Perspectivementioning
confidence: 99%
“…Anti-cancer nanomedicines are rapidly emerging as a promising approach and offers the possibilities to the clinicians to overcome the limitations of current cancer therapy. [14][15][16][17] In this direction, an array of nanomedicines has been synthesized, engineered with different physiochemical properties, such as size, shape and surface chemistry, and formulated with a large variety of anti-cancer therapeutics, including surface modifications with, e.g., polyethylene glycol (PEG) or other coatings, in order to extend the circulation time of the nanomedicines in bloodstream. [18][19][20] Various targeting moieties, such as antibodies, peptides, sugars and proteins, have also been attached to nanomedicines in different ways to further facilitate their selective accumulation within the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The role of nanomedicine in the targeting process has been relevant 4, 5, 6. Indeed, in the last two decades, a broad range of nanomaterials has been developed for targeted therapies.…”
mentioning
confidence: 99%